A solid-state polymer electrolyte of ortho-hydroxyl calix[4]pyrrole modified PVDF and a preparation method and application thereof
Patent Information
- Application Number
- CN202611038489.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-10-23
AI Technical Summary
[0004]然而,现有PVDF基聚合物电解质仍存在若干亟待解决的技术问题:其一,其室温离子电导率相对较低,限制了电池的倍率性能与功率密度;其二,聚合物电解质与电极之间的界面稳定性较差,长期循环过程中界面阻抗持续增大,影响电池的循环寿命与倍率性能;其三,在PVDF基聚合物电解质的制备过程中,通常需要使用N,N-二甲基甲酰胺(DMF)等高介电常数极性溶剂溶解PVDF并辅助锂盐解离,但即使经过真空干燥处理,电解质膜中仍会残留一定量的DMF溶剂分子
(1)本发明通过在PVDF基聚合物电解质中引入邻羟基杯[4]吡咯添加剂,利用其大环空腔内的N-H官能团与残留DMF溶剂分子形成强氢键主客体相互作用,有效锚定自由DMF分子,显著抑制了其随锂离子迁移至电极表面所引发的副反应与腐蚀,腐蚀电流密度显著降低;同时,添加剂分子末端的酚羟基氧原子可与锂离子发生特异性配位,促进锂盐充分解离,将锂离子迁移数提升,并提高了电解质的离子电导率。
Smart Images

Figure CN122968424A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery electrolyte technology, and in particular to an ortho-hydroxycalix[4]pyrrole-modified polyvinylidene fluoride (PVDF)-based solid polymer electrolyte and its preparation method, as well as the application of the electrolyte in lithium metal batteries and lithium-ion batteries. Background Technology
[0002] With the rapid development of new energy vehicles, portable electronic devices, and renewable energy storage systems, increasingly higher demands are being placed on the energy density, safety, and cycle life of rechargeable batteries. While traditional liquid electrolyte lithium-ion batteries exhibit excellent energy density and rate performance, the flammability and leakage risks associated with liquid organic electrolytes severely limit their application in high-safety-critical scenarios. Solid-state electrolytes, due to their absence of flammable liquid components, are considered an effective way to improve battery safety and have received widespread attention.
[0003] Among various solid electrolyte systems, PVDF-based polymer electrolytes have become one of the hot topics in solid electrolyte research due to their excellent electrochemical stability, good mechanical strength, and good compatibility with positive and negative electrode materials.
[0004] However, existing PVDF-based polymer electrolytes still face several pressing technical challenges: First, their relatively low room-temperature ionic conductivity limits the battery's rate performance and power density. Second, the interface stability between the polymer electrolyte and the electrode is poor, with interfacial impedance continuously increasing during long-term cycling, affecting the battery's cycle life and rate performance. Third, the preparation of PVDF-based polymer electrolytes typically requires the use of high-dielectric-constant polar solvents such as N,N-dimethylformamide (DMF) to dissolve PVDF and assist in lithium salt dissociation. However, even after vacuum drying, a certain amount of DMF solvent molecules remain in the electrolyte membrane. These unbound "free" DMF molecules migrate with lithium ions to the lithium metal anode surface during battery charging and discharging, where they undergo continuous reduction and decomposition side reactions. This leads to instability at the solid electrolyte interface, increased interfacial impedance, and reduced coulombic efficiency, ultimately resulting in poor battery cycle life and even short circuits.
[0005] In existing technologies, researchers have attempted to improve the performance of PVDF-based polymer electrolytes by introducing additives such as inorganic fillers, ionic liquids, or organic molecules. However, most existing additives can only improve ionic conductivity or mechanical properties to a certain extent, and it is difficult to simultaneously and effectively inhibit the migration behavior of residual free solvent molecules, nor can they simultaneously promote the dissociation of lithium salts, resulting in limited modification effects. Therefore, there is an urgent need to develop a novel additive and a corresponding polymer electrolyte system that can simultaneously achieve the dual functions of "solvent molecule anchoring" and "promoting lithium salt dissociation" to fundamentally solve the problem of poor cycle stability caused by residual solvent side reactions. Summary of the Invention
[0006] In view of the shortcomings of the prior art, the purpose of this invention is to provide a PVDF-based solid polymer electrolyte modified with ortho-hydroxycalix[4]pyrrole, its preparation method and application.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: A PVDF-based solid polymer electrolyte modified with o-hydroxycalix[4]pyrrole includes a PVDF matrix, a lithium salt and o-hydroxycalix[4]pyrrole additive, wherein the o-hydroxycalix[4]pyrrole is a macrocyclic structure consisting of four pyrrole units and four racemic carbon atoms connected alternately, and the racemic carbon atoms are connected with 3,4-dihydroxyphenyl and a methyl group.
[0008] Based on the above technical solutions, preferably, the lithium salt accounts for 35% to 45% of the mass of the PVDF, and the ortho-hydroxycalix[4]pyrrole accounts for 5% to 25% of the mass of the PVDF.
[0009] Based on the above technical solutions, preferably, the preparation method of the o-hydroxycalix[4]pyrrole includes: dissolving pyrrole and 3,4-dihydroxyacetophenone in an organic solvent, adding a catalyst, and reacting to obtain the o-hydroxycalix[4]pyrrole.
[0010] Based on the above technical solutions, preferably, the molar ratio of pyrrole to 3,4-dihydroxyacetophenone is 0.95 to 1.05:1.
[0011] Based on the above technical solutions, preferably, the organic solvent is selected from any one or a mixture of two of methanol and ethanol.
[0012] Based on the above technical solutions, preferably, the catalyst is selected from at least one of methanesulfonic acid, trifluoroacetic acid, and hydrochloric acid, and the molar ratio of the catalyst to 3,4-dihydroxyacetophenone is 0.45 to 0.55:1.
[0013] Based on the above technical solutions, preferably, the reaction temperature is 15-30℃ and the time is 8-24h.
[0014] Based on the above technical solutions, preferably, the lithium salt is selected from at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethyl)sulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium perchlorate.
[0015] The present invention also provides a method for preparing the PVDF-based solid polymer electrolyte, comprising the following steps: adding PVDF, lithium salt and o-hydroxycalix[4]pyrrole to N,N-dimethylformamide solvent according to the ratio, stirring to dissolve, and allowing to stand to degas to obtain an electrolyte slurry; casting the electrolyte slurry into a film, and drying it under vacuum to obtain the PVDF-based solid polymer electrolyte.
[0016] The present invention also provides an application of the PVDF-based solid polymer electrolyte in lithium metal batteries or lithium-ion batteries.
[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention introduces an ortho-hydroxycalix[4]pyrrole additive into a PVDF-based polymer electrolyte. The NH functional group in the macrocyclic cavity of the additive forms a strong hydrogen bond host-guest interaction with the residual DMF solvent molecules, effectively anchoring the free DMF molecules and significantly suppressing the side reactions and corrosion caused by the migration of DMF molecules to the electrode surface with lithium ions. The corrosion current density is significantly reduced. At the same time, the phenolic hydroxyl oxygen atom at the end of the additive molecule can specifically coordinate with lithium ions, promote the full dissociation of lithium salt, increase the lithium ion migration number, and improve the ionic conductivity of the electrolyte.
[0018] (2) In this invention, the abundant ortho-hydroxyl groups at the end of the ortho-hydroxy calix [4] pyrrole molecule can form a hydrogen bond network with the fluorine atoms on the PVDF molecular chain, which enhances the interaction between polymer molecular chains and improves the mechanical flexibility and processing performance of the electrolyte membrane.
[0019] (3) The Li||Li symmetric battery assembled using the polymer electrolyte of the present invention can effectively suppress the formation of lithium dendrites and dead lithium, achieve long-term stable cycling, and has excellent critical current density performance; the assembled Li||LiFePO4 button battery exhibits excellent long-cycle stability and extremely high coulombic efficiency; the assembled soft-pack battery can still stably power LED lights after multiple bends, showing excellent flexibility and practicality, and has good prospects for industrial application. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 This is a schematic diagram of the mechanism of action of the PVDF-based polymer electrolyte modified with ortho-hydroxycalix[4]pyrrole in this invention; Figure 2 The proton NMR spectrum of C4P-1 prepared in Example 1; Figure 3 The ionic conductivity of the stainless steel symmetric cells assembled using Examples 1-5 and Comparative Example 1 is shown. Figure 4 The tV curves are obtained from the constant current cycling test of the Li||Li symmetric cells assembled in Example 1 and Comparative Example 1. Figure 5 The graph shows the rate performance (tV) curves of the Li||Li symmetric cells assembled in Example 1 and Comparative Example 1. Figure 6 The critical current density test tV curves of the Li||Li symmetric cells assembled in Example 1 and Comparative Example 1 are shown. Figure 7 The it curve and Nyquist curve of AC impedance test are shown for the Li||Li symmetric cells assembled in Example 1 and Comparative Example 1. Figure 8 Tafel curves of the Li||Li symmetric cells assembled in Example 1 and Comparative Example 1; Figure 9 The graph shows the charge-discharge cycle performance of the Li||LiFePO4 button cells assembled in Example 1 and Comparative Example 1. Figure 10 The charge-discharge curves of the Li||LiFePO4 button batteries assembled in Example 1 and Comparative Example 1 are shown. Figure 11 The graph shows the charge-discharge cycle performance of the Li||LiFePO4 pouch cells assembled in Example 1 and Comparative Example 1. Figure 12 The photo shows the red LED light up after the Li||LiFePO4 pouch battery assembled in Example 1 is folded in half and three times. Detailed Implementation
[0022] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0023] Specifically, the ortho-hydroxycalix[4]pyrrole (C4P-1) is an organic supramolecular compound with a macrocyclic structure. Its macrocyclic skeleton is composed of 4 pyrrole units and 4 racemic carbon atoms connected alternately. Each racemic carbon atom is connected to a methyl substituent and a 3,4-dihydroxyphenyl substituent. There are 4 NH functional groups derived from the pyrrole ring arranged inside the macrocyclic cavity, and 8 phenolic hydroxyl functional groups are distributed on the outer edge of the macrocyclic ring. That is, each 3,4-dihydroxyphenyl contains 2 adjacent hydroxyl groups.
[0024] The polymer electrolyte also contains residual DMF solvent, which accounts for 5 wt% to 25 wt% of the total electrolyte mass. At least some of the DMF solvent molecules are anchored and confined within the macrocyclic cavity through hydrogen bond host-guest interactions with the NH functional groups in the C4P-1 macrocyclic cavity, thus suppressing the side reactions caused by the migration of lithium ions to the electrode surface during charging and discharging.
[0025] Figure 1 This is a schematic diagram illustrating the mechanism by which C4P-1 anchors residual DMF solvent molecules and modifies PVDF-based polymer electrolytes according to the present invention; wherein, 1 is a PVDF molecular chain, 2 is a fluorine atom on the PVDF molecular chain, 3 is the C4P-1 macrocyclic skeleton, 4 is an NH functional group in the macrocyclic cavity, 5 is a hydroxyl functional group at the end of the C4P-1 molecule, 6 is a DMF solvent molecule anchored and confined in the macrocyclic cavity, and 7 is a lithium ion.
[0026] Specifically, the terminal hydroxyl group of C4P-1 forms a hydrogen bond with the fluorine atom on the PVDF molecular chain; the hydroxyl oxygen atom of C4P-1 undergoes a coordination interaction with lithium ions, thereby promoting the dissociation of lithium salt and increasing the lithium ion transference number and the ionic conductivity of the electrolyte.
[0027] The preparation method of C4P-1 specifically includes: S1, adding PVDF, lithium salt and C4P-1 to 3.2 mL DMF in a set ratio, stirring at 40-80℃ until completely dissolved to form a uniform electrolyte slurry; S2, casting the electrolyte slurry onto a clean mold surface to form a wet film; S3, placing the wet film in a vacuum drying oven and vacuum drying at 60-90℃ for 6-24 hours to remove some of the free DMF solvent, obtaining the PVDF-based solid polymer electrolyte membrane with a thickness of 20-200 μm, wherein the electrolyte membrane retains some residual DMF molecules anchored and restricted by C4P-1.
[0028] Specifically, the PVDF-based solid polymer electrolyte membrane can be used in batteries such as Li||Li symmetric cells, Li||LiFePO4 full cells, or lithium metal batteries or lithium-ion batteries. The battery form can be a button cell or a pouch cell.
[0029] It should be noted that, unless otherwise specified, the raw materials used in the embodiments are all commercially available conventional products or synthesized from commercially available conventional products, and the methods used are all conventional methods in the art.
[0030] Example 1 This embodiment provides a method for preparing a PVDF-based solid polymer electrolyte modified with o-hydroxycalix[4]pyrrole, comprising the following steps: 1.00 g PVDF, 0.40 g lithium bis(fluorosulfonyl)imide and 0.2 g C4P-1 are added to 3.2 mL DMF and magnetically stirred at 60°C for 4 hours until completely dissolved to obtain a uniform, semi-transparent electrolyte slurry; the slurry is cast onto a clean polytetrafluoroethylene mold surface and allowed to stand at room temperature to allow some of the solvent to initially evaporate and form a film; the resulting film is then transferred to a vacuum drying oven and vacuum dried at 70°C for 12 hours to obtain a C4P-1 modified PVDF-based solid polymer electrolyte membrane with a thickness of about 60 micrometers.
[0031] The preparation method of C4P-1 is as follows: Add 15.22 g (0.10 mol) of 3,4-dihydroxyacetophenone, 6.70 mL (0.10 mol) of pyrrole, and 250.00 mL of anhydrous methanol to a 500 mL round-bottom flask. After the raw materials are completely dissolved, purge the nitrogen atmosphere at least three times using an oil pump and a double-row tube. Draw methanesulfonic acid (4.81 g, 0.050 mol) into a syringe and slowly inject it into the reaction flask under a nitrogen atmosphere, then purge the nitrogen atmosphere again. The reaction is then carried out at room temperature (25 °C) under a nitrogen atmosphere for 16 h. When the reaction is complete, ammonia is slowly introduced dropwise into the reaction solution with stirring, and the pH value is monitored in real time until it is in the weakly alkaline range of 7.00–8.00 (measured at 7.61). Purification is performed using rapid silica gel column chromatography with methanol as the eluent. The eluent is then subjected to rotary evaporation to remove residual solvent. 80.00 mL of glacial acetic acid was added to the crude extract, and the mixture was heated to dissolve it. The extract was then allowed to stand at room temperature for crystallization. After the precipitate had completely formed, it was purified by vacuum filtration to obtain C4P-1.
[0032] like Figure 2 As shown, the proton nuclear magnetic resonance spectrum (NMR) 1 ¹H NMR confirmation: NMR data further verified the host-guest interaction between C4P-1 and DMF solvent molecules. The free host C4P-1 exhibits a signal peak at approximately 8.78 ppm, which is the active hydrogen atom on the NH group of pyrrole. Upon addition of DMF, this signal peak shifts significantly to the lower field left to approximately 9.34 ppm, as indicated by the arrow. The electronegativity of the oxygen atom reduces the electron cloud density on the NH bond, leading to a lower field shift in the proton resonance frequency. The lower field shift from 8.78 ppm to 9.34 ppm is due to the hydrogen bonding interaction between C4P-1 and DMF in solution. The proton signals on the benzene and pyrrole rings of the C4P-1 molecule in solution are averaged or broadened. After binding with DMF, a slight shift occurs in the signal positions of the protons on the pyrrole ring and the benzene ring around 5.96 ppm. The DMF signal changes show the aldehyde protons in pure DMF; the top spectrum shows the aldehyde protons in pure DMF at approximately 7.97 ppm. In the intermediate mixture spectrum, this peak still exists around 7.97 ppm, indicating that DMF is indeed present in the system. The ortho-hydroxycalix[4]pyrrole host successfully recognizes and encapsulates the DMF molecule through multiple hydrogen bonds formed with NH.
[0033] Example 2 This embodiment provides a method for preparing a PVDF-based solid polymer electrolyte modified with o-hydroxycalix[4]pyrrole, comprising the following steps: 1.00 g PVDF, 0.35 g lithium difluorosulfonylimide and 0.05 g C4P-1 are added to 3.2 mL DMF and magnetically stirred at 60°C for 4 hours until completely dissolved to obtain a uniform, semi-transparent electrolyte slurry; the slurry is cast onto a clean polytetrafluoroethylene mold surface and allowed to stand at room temperature to allow some of the solvent to initially evaporate and form a film; the resulting film is then transferred to a vacuum drying oven and vacuum dried at 70°C for 12 hours to obtain a C4P-1 modified PVDF-based solid polymer electrolyte membrane with a thickness of about 60 micrometers.
[0034] The preparation method of C4P-1 is as follows: Add 15.22 g (0.10 mol) of 3,4-dihydroxyacetophenone, 6.37 mL (0.095 mol) of pyrrole, and 250.00 mL of anhydrous methanol to a 500 mL round-bottom flask. After the raw materials are completely dissolved, purge the nitrogen atmosphere three times or more using an oil pump and a double-row tube. Draw methanesulfonic acid (4.33 g, 0.45 mol) into a syringe and slowly inject it into the reaction flask under a nitrogen atmosphere, then purge the nitrogen atmosphere again. The reaction is then carried out at room temperature (25 °C) under a nitrogen atmosphere for 24 h. When the reaction is complete, ammonia is slowly introduced dropwise into the reaction solution with stirring, and the pH value is monitored in real time until it is in the weakly alkaline range of 7.00–8.00 (measured at 7.83). Purification is performed using rapid silica gel column chromatography with methanol as the eluent. The eluent is then subjected to rotary evaporation to remove residual solvent. 80.00 mL of glacial acetic acid was added to the crude extract, and the mixture was heated to dissolve it. The extract was then allowed to stand at room temperature for crystallization. After the precipitate had completely formed, it was purified by vacuum filtration to obtain C4P-1.
[0035] Example 3 This embodiment provides a method for preparing a PVDF-based solid polymer electrolyte modified with o-hydroxycalix[4]pyrrole, comprising the following steps: 1.00 g PVDF, 0.45 g lithium difluorosulfonylimide and 0.25 g C4P-1 are added to 3.2 mL DMF and magnetically stirred at 60°C for 4 hours until completely dissolved to obtain a uniform, semi-transparent electrolyte slurry; the slurry is cast onto a clean polytetrafluoroethylene mold surface and allowed to stand at room temperature to allow some of the solvent to initially evaporate and form a film; the resulting film is then transferred to a vacuum drying oven and vacuum dried at 70°C for 12 hours to obtain a C4P-1 modified PVDF-based solid polymer electrolyte membrane with a thickness of about 60 micrometers.
[0036] The preparation method of C4P-1 is as follows: Add 15.22 g (0.10 mol) of 3,4-dihydroxyacetophenone, 7.04 mL (0.105 mol) of pyrrole, and 250.00 mL of anhydrous methanol to a 500 mL round-bottom flask. After the raw materials are completely dissolved, purge the nitrogen atmosphere three times or more using an oil pump and a double-row tube. Draw methanesulfonic acid (5.29 g, 0.55 mol) into a syringe and slowly inject it into the reaction flask under a nitrogen atmosphere, then purge the nitrogen atmosphere again. The reaction is then carried out at room temperature (25 °C) under a nitrogen atmosphere for 8 hours. When the reaction is complete, ammonia is slowly introduced dropwise into the reaction solution with stirring, and the pH value is monitored in real time until it is in the weakly alkaline range of 7.00–8.00 (measured at 7.39). Purification is performed using rapid silica gel column chromatography with methanol as the eluent. The eluent is then subjected to rotary evaporation to remove residual solvent. 80.00 mL of glacial acetic acid was added to the crude extract, and the mixture was heated to dissolve it. The extract was then allowed to stand at room temperature for crystallization. After the precipitate had completely formed, it was purified by vacuum filtration to obtain C4P-1.
[0037] Example 4 This embodiment provides a method for preparing a PVDF-based solid polymer electrolyte modified with ortho-hydroxycalix[4]pyrrole, which is the same as in Example 1, except that the amount of C4P-1 added is 0.1g.
[0038] Example 5 This embodiment provides a method for preparing a PVDF-based solid polymer electrolyte modified with ortho-hydroxycalix[4]pyrrole, which is the same as in Example 1, except that the amount of C4P-1 added is 0.15g.
[0039] Comparative Example 1 1.00 g of PVDF and 0.40 g of lithium difluorosulfonamide were added to 8 mL of DMF and magnetically stirred at 60 °C for 4 hours until completely dissolved to obtain a uniform, semi-transparent electrolyte slurry. The slurry was cast onto the surface of a clean polytetrafluoroethylene mold and allowed to stand at room temperature to allow some of the solvent to evaporate and form a film. The resulting film was then transferred to a vacuum drying oven and vacuum dried at 70 °C for 12 hours to obtain a PVDF-based solid polymer electrolyte membrane with a thickness of approximately 60 micrometers.
[0040] Performance testing and results analysis (1) Stainless steel || Assembly and performance testing of stainless steel symmetrical batteries The method for testing ionic conductivity typically employs AC impedance spectroscopy. First, PVDF-based solid polymer electrolyte samples with different C4P-1 addition contents are prepared and fabricated into test specimens of suitable shape and size, ensuring a smooth, defect-free surface and uniform thickness. The specimens are then placed between two parallel electrodes to form a test cell, using inert electrodes (stainless steel electrodes) to avoid interference from electrode reactions. Next, the test cell is connected to an electrochemical workstation, and AC impedance spectroscopy is performed at room temperature to obtain the electrolyte's bulk resistance (Rb). Combining this with the specimen thickness (d) and the contact area between the electrode and the specimen (A), the ionic conductivity of the sample is calculated using the formula σ = d / (Rb×A) (where σ is the ionic conductivity). Repeating the above test steps for samples with different C4P-1 addition contents yields the ionic conductivity data for different C4P-1 addition contents. Figure 3 As shown.
[0041] from Figure 3 As can be seen, the stainless steel symmetrical batteries assembled using Examples 1 (20%), 2 (5%), 3 (25%), 4 (10%), 5 (15%), and Comparative Example 1 (0%) exhibited a trend of first increasing and then decreasing ionic conductivity as the content of C4P-1 in the PVDF polymer electrolyte increased. When the content gradually increased from 0% to 20%, the ionic conductivity gradually increased, reaching its maximum at 20%; however, when the content continued to increase to 25%, the ionic conductivity began to decrease.
[0042] (2) Assembly and performance testing of Li||Li symmetric cells Using the C4P-1 modified PVDF-based solid polymer electrolyte membrane prepared in Example 1 and the PVDF-based solid polymer electrolyte membrane prepared in Comparative Example 1 as separators and electrolyte layers respectively, and lithium metal sheets as positive and negative electrodes, Li||Li symmetric cells were assembled.
[0043] Constant current cycling test: at 0.1 mA cm⁻¹ -2 0.1 mAh cm -2 Constant current cycling tests were performed under constant current conditions, and the time-voltage curve (tV curve) is shown below. Figure 4 As shown.
[0044] from Figure 4 As can be seen, the Li||Li symmetric cell assembled using Example 1 can achieve stable cycling for more than 2000 hours with a stable polarization voltage; while the Li||Li symmetric cell assembled using Comparative Example 1 shows a significant increase in polarization voltage in less than 200 hours and a short circuit occurs at about 300 hours.
[0045] Rate cycling test: The test was conducted at 25 °C, with an initial rate of 0.1 mA cm⁻¹. -2 The current density was used for constant current charge-discharge cycling, with a fixed areal capacity of 0.1 mAh cm⁻¹ for each cycle. -2 The voltage-time curve was recorded. After at least 5 stable cycles, the current density was increased to 0.2 mA cm⁻¹. -2 The cycle was continued, and the voltage polarization was observed to increase significantly or exhibit abnormal fluctuations. The voltage was then increased sequentially to 0.3, 0.4, and 0.5 mA cm⁻¹. -2 The same number of cycles and areal capacity were maintained at each current density until all gradient tests were completed. This was done within the range of 0.1–0.5 mA cm⁻¹. -2 In the rate cycling test at gradient current density, the Li||Li symmetric cell assembled in Example 1 consistently maintained a low and stable polarization voltage, such as... Figure 5 .
[0046] Critical current density test: During the test, a fixed areal capacity (e.g., 0.1 mAh·cm³) is used. -2 The system performs charge-discharge cycles, typically with an initial current density set to a low value. After each one or several cycles, the current density is increased in preset steps (0.1 mA / cm²). -2 Increasing current density. At each current density, the battery must be cycled stably for at least 10 cycles to eliminate randomness and observe the overpotential trend. When the battery voltage suddenly drops to near zero (below 10 mV) or significant noise or abnormal voltage plateau fluctuations occur, a short circuit is determined, and the corresponding current density is the critical current density. Critical current density test results. Figure 6 This indicates that the critical current density of the Li||Li symmetric cell assembled using Example 1 can reach 2.5 mA cm⁻¹. -2 This is significantly better than the Li||Li symmetric cell assembled using Comparative Example 1 (1.5 mA cm⁻¹). -2 ).
[0047] Lithium-ion transport number testing: The Bruce-Vincent method was used. First, the Li||Li symmetric battery assembled in Example 1 was left to stand at room temperature for approximately 6 hours for the first AC impedance test. The frequency range was set from 1 MHz to 0.1 Hz, and an AC amplitude of 10 mV was applied to obtain the initial total battery impedance R0, which includes the electrolyte bulk resistance and the electrode / electrolyte interface impedance. Immediately afterwards, the method was switched to chronoamperometry (it curve), and a constant DC voltage of 10 mV was applied. The change in current over time was recorded until the current stabilized, and the initial current I0 and the steady-state current I0 were read. s Finally, the AC impedance test was performed again, with parameters exactly the same as the first time, to obtain the polarized impedance R.s .
[0048] like Figure 7 As shown, Figure 7 a and Figure 7 b shows the it curve and Nyquist curve of the AC impedance test for the Li||Li symmetric cells assembled using Example 1 and Comparative Example 1. Figure 7 c and Figure 7 Figure d shows the it curve and Nyquist curve of the AC impedance test for the Li||Li symmetric cells assembled using Example 1 and Comparative Example 1. Substituting the measured parameters into the Bruce-Vincent-Evans correction formula, the lithium-ion transference number of the electrolyte was calculated. The lithium-ion transference numbers of the Li||Li symmetric cells assembled using Example 1 and Comparative Example 1 were approximately 0.61 and 0.28, respectively.
[0049] Tafel curve test: The steady-state polarization method was used to test the Tafel curve. The potential scan range was ±300 mV relative to the open circuit potential, and the scan rate was 0.5 mV / s. The polarization potential and response current were recorded, and the Tafel curve was obtained by plotting the logarithm of the absolute value of the current against the polarization potential.
[0050] Tafel curve as shown Figure 8 As shown, the corrosion current density of the Li||Li symmetric cell assembled in Example 1 is 0.10 mAcm⁻¹. -2 The corrosion current density of the Li||Li symmetric cell assembled in Comparative Example 1 is 0.26 mA cm⁻¹. -2 .
[0051] (3) Assembly and performance testing of Li||LiFePO4 button cells Using the C4P-1 modified PVDF-based solid polymer electrolyte membrane prepared in Example 1 and the PVDF-based solid polymer electrolyte membrane prepared in Comparative Example 1 as electrolyte layers, LiFePO4 as the positive electrode and lithium metal sheet as the negative electrode, Li||LiFePO4 button cells were assembled.
[0052] Charge-discharge cycle test: Charge-discharge cycle tests were conducted at 1C rate and room temperature. The test results are as follows: Figure 9 As shown.
[0053] from Figure 9 As can be seen, the initial discharge capacity of the Li||LiFePO4 coin cell assembled using Example 1 is approximately 150 mAh g. -1After 1400 cycles, the capacity retention rate can still reach over 87.3%, and the coulombic efficiency remains close to 100%; while the Li||LiFePO4 coin cell assembled using Comparative Example 1 shows rapid capacity decay after about 300 cycles.
[0054] Charge-discharge curves as follows Figure 10 As shown, a Li||LiFePO4 coin cell assembled using Comparative Example 1 ( Figure 10 a) As the polarization voltage difference in the charge-discharge curve widens during cycling, the voltage plateau becomes severely deformed by the 350th cycle, reflecting the runaway growth of its internal ohmic impedance and charge transfer impedance. The Li||LiFePO4 coin cell assembled in Example 1 ( Figure 10 b) After 1400 cycles, its charge-discharge curves still maintain a high degree of overlap, and the flat voltage plateau hardly increases.
[0055] (4) Assembly and performance testing of Li||LiFePO4 pouch cells Using the C4P-1 modified PVDF-based solid polymer electrolyte membrane prepared in Example 1 and the PVDF-based solid polymer electrolyte membrane prepared in Comparative Example 1 as electrolyte layers, LiFePO4 as the positive electrode and lithium metal sheet as the negative electrode, Li||LiFePO4 soft-pack batteries were assembled.
[0056] Charge-discharge cycle test: Cyclic tests were conducted at a 0.5C rate, and the test results are as follows. Figure 11 As shown.
[0057] from Figure 11 As can be seen, the Li||LiFePO4 pouch cell assembled using Example 1 still exhibits excellent capacity retention after 120 cycles.
[0058] After connecting the Li||LiFePO4 pouch battery assembled in Example 1 to a red LED light, it could still provide stable power to the LED even after diagonal folding and multiple bends, demonstrating excellent mechanical flexibility and safety in use. Figure 12 As can be seen in (a) and (b), the battery did not experience any open circuit or short circuit under the harsh conditions of diagonal folding or three bends, and it was still able to continuously light up the red LED.
[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A PVDF-based solid polymer electrolyte modified with o-hydroxycalix[4]pyrrole, characterized in that, It includes a PVDF matrix, lithium salt and o-hydroxycalix[4]pyrrole additive, wherein the o-hydroxycalix[4]pyrrole is a macrocyclic structure consisting of 4 pyrrole units and 4 racemic carbon atoms connected alternately, and the racemic carbon atoms are connected to 3,4-dihydroxyphenyl and a methyl group.
2. The PVDF-based solid polymer electrolyte according to claim 1, characterized in that, The lithium salt accounts for 35% to 45% of the mass of PVDF, and the o-hydroxycalix[4]pyrrole accounts for 5% to 25% of the mass of PVDF.
3. The PVDF-based solid polymer electrolyte according to claim 1, characterized in that, The preparation method of the o-hydroxycalix[4]pyrrole includes: dissolving pyrrole and 3,4-dihydroxyacetophenone in an organic solvent, adding a catalyst, and reacting to obtain the o-hydroxycalix[4]pyrrole.
4. The PVDF-based solid polymer electrolyte according to claim 3, characterized in that, The molar ratio of pyrrole to 3,4-dihydroxyacetophenone is 0.95 to 1.05:
1.
5. The PVDF-based solid polymer electrolyte according to claim 3, characterized in that, The organic solvent is selected from any one or a mixture of two of methanol and ethanol.
6. The PVDF-based solid polymer electrolyte according to claim 3, characterized in that, The catalyst is selected from at least one of methanesulfonic acid, trifluoroacetic acid, and hydrochloric acid, and the molar ratio of the catalyst to 3,4-dihydroxyacetophenone is 0.45 to 0.55:
1.
7. The PVDF-based solid polymer electrolyte according to claim 3, characterized in that, The reaction is carried out at a temperature of 15–30°C for 8–24 hours.
8. The PVDF-based solid polymer electrolyte according to claim 1, characterized in that, The lithium salt is selected from at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethyl)sulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium perchlorate.
9. A method for preparing a PVDF-based solid polymer electrolyte as described in any one of claims 1-8, characterized in that, The steps include: adding PVDF, lithium salt and o-hydroxycalix[4]pyrrole to N,N-dimethylformamide solvent according to the ratio, stirring to dissolve, and letting stand to degas to obtain electrolyte slurry; casting the electrolyte slurry into a film, and drying it under vacuum to obtain the PVDF-based solid polymer electrolyte.
10. The application of a PVDF-based solid polymer electrolyte as described in any one of claims 1-8 in a lithium metal battery or a lithium-ion battery.